1975
DOI: 10.1029/wr011i001p00001
|View full text |Cite
|
Sign up to set email alerts
|

An economic analysis of water resource investments and regional economic growth

Abstract: The purpose of this paper is to analyze the effects of the Bureau of Reclamation's water resource projects over the period 1930-1970 on regional economic growth in the Southwest. The empirical results indicate that these investments have had an impact on regional economic growth and that the extent of the effect depends on the nature of the water investment, the state of the regional economy, and the amount and nature of other investments in the region. Study Area Geographic Region Lower Colorado region Arizon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1977
1977
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The benefit of stimulating the development of regional economy by hydropower development is well studied both qualitatively [30] and quantitatively [31][32][33], but they only studied the driving effect of a project on the growth of economic aggregate, which is not the external effect of economic growth. By using the theory of Pigovian Tax [34], the external benefit of simulating the development of regional economy is measured by the actual return when using tax revenue as the investment.…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of stimulating the development of regional economy by hydropower development is well studied both qualitatively [30] and quantitatively [31][32][33], but they only studied the driving effect of a project on the growth of economic aggregate, which is not the external effect of economic growth. By using the theory of Pigovian Tax [34], the external benefit of simulating the development of regional economy is measured by the actual return when using tax revenue as the investment.…”
Section: Discussionmentioning
confidence: 99%
“…Although my inference is not based on a formal meta-analysis, the large majority of behavior-based (inductive) valuations in the literature appear to show a much lower valuation than do those grounded on the more common deductive models that relied on hypothesized producer actions. A few econometric examples that show results much less optimistic for returns to public irrigation investments than do the deductive analyses commonly used for ex ante justification of such investments include: analyses of the contribution of irrigation to farm land values (see Torell et al 1990); studies of regional economic impacts of irrigation in the western US (Cicchetti et al 1975); econometric evaluations of factors (including investments in irrigation infrastructure) affecting regional long term economic growth in India and China (Fan and Hazell 2002); and ex post studies of public irrigation water investments in the western US (Wilson 1997). Further evidence is the general inability of governments to collect a significant part of the cost of public irrigation investments.…”
Section: Issue: Conflicts Between Deductive and Inductive Resultsmentioning
confidence: 99%
“…A similar study by Fullerton et al (1975) of counties in seven western states found no relationship between water investment and economic growth. Cicchetti et al (1975) extended this study using economic subregions as the unit of analysis and found that variables representing federal investment in irrigation facilities had no significant impact on regional income and growth, and only a small and not convincingly significant impact on the value of farm output. There was some relationship between economic growth and federal investments in flood control, hydropower, and recreation, but the coefficients were often unstable.…”
Section: Introductionmentioning
confidence: 91%